Molecular characterization of Tomato yellow leaf curl (TYLCV) and its vector (Bemisia tabaci) - Barbar, Aqeel Nazzal; Abbas, Zianab M. (Journal of Kerbala for Agricultural Sciences, 2018)
The aim of this study was to isolate and diagnose two different isolates of Tomato yellow leaf curl virus (TYLCV) and to investigate the biotype of whiteflies insects (Bemisia tabaci) using the polymerase chain reaction technique to determine the sequences of the nitrogen bases of the PCR-amplified products to identify the genetic similarity and differences between the virus isolates as well as among the biotypes of whiteflies (B. tabaci) spread in the sampling areas in some of the provinces of Iraq (Najaf, Karbala, Babylon and Dewanyia) in addition to know which of them are more prevalent in those areas. Results of the polymerase chain reaction (PCR) test using the TY1 and TY2 primers showed the possibility of amplifying a PCR product of 580 base pairs (bp) from the TYLCV isolates obtained from some areas in the provinces of Najaf, Babylon. It was also found from the results of the analysis of the mitochondrial cytochrome oxidize I (mtCOI) sequences generated from the PCR-amplified products amplified from B. tabaci samples collected from different regions in Najaf, Karbala, Babylon and Diwaniya governorates, that the biotype B is the only biotype identified in this study, which makes the presence and dominance of this biotype more dangerous in the spread of TYLCV in nature for being one of the two biotypes of this insect that is responsible for the transmission of TYLCV.